A Conceptual Framework for Early Identification of Elementary School-Age Students at Risk for Language and Literacy Disorders: A Pilot Study (Journal of Education and Development, 2024)
Purpose: This study sought answers to the following questions: (1) How do teachers describe the effectiveness of the conceptual framework in the early identification of at-risk children? (2) What is the impact of narrative language interventions on language and reading comprehension? Method: Using Narrative Language Measures (NLM) subtests, students (age ranges 5 – 7 years) were identified as at-risk for language and literacy disorders. Thirty kindergarten and first-grade students and their teachers participated in the study. The experimental group received narrative language interventions, following which both the experimental and control groups were re-screened using NLM subtests. Student modifiability ratings were completed at the end of the first and last intervention sessions to study changes in the experimental group’s narrative language ability in response to direct language interventions. The teachers completed questionnaires to subjectively rate the experimental group’s skill set pre-and post-intervention. Results: The teacher-completed questionnaires indicated that the students’ skillset post versus pre-intervention was not statistically significant. The teachers agreed that the conceptual framework was useful in the early identification of at-risk students. The experimental group had significantly higher scores post-intervention in NLM Listening than did the control group. There was no significant difference in NLM Reading scores between the experimental and control groups at baseline and post intervention; however, there was a significant increase in scores within the experimental group pre- and post-intervention. Conclusions: Communication between teachers and speech language pathologists can be a useful tool in the early identification of children at-risk for language and literacy disorders. Narrative language interventions have a positive impact on language and reading comprehension.